Implementation of Management for the Handling of People with Mental Disorders: JEL Classification: I18, H75, H83, I31, D73 - Edy Rahman; Muhammad Ridwan; Jamaluddin Sawaji (Newinera Publisher, 2026)
This research is motivated by the suboptimal governance of the management of People with Mental Health Problems (ODMK) in Nunukan Regency, characterized by weak inter-agency coordination and overlapping authority in carrying out tasks in the field. The complexity of ODMK problems requires the involvement of various parties, such as the Social Service, Health Service, Community Health Centers, Public Order Agency (Satpol PP), and the Police. However, the absence of an integrated mechanism regulating the roles of each agency results in inefficient, often interdependent, and unsustainable handling processes. The focus of this research is to examine the implementation of ODMK management and identify the obstacles faced by agencies in implementing integrated handling. This research uses a qualitative approach with a descriptive approach. Data collection techniques were conducted through in-depth interviews with informants from various relevant agencies, such as the Social Services Agency, Community Health Centers, the Police, the Public Order Agency (Satpol PP), and community members. Data were also supported by documentation studies and a review of supporting literature. The results indicate that the implementation of governance for the management of ODMK has not been optimal. Management functions such as planning, organizing, implementing, and monitoring have not been optimally implemented due to the lack of standard operating procedures (SOPs). This situation results in incidental handling of people with mental health problems, minimal coordination, and a risk of human rights violations. Furthermore, structural and technical obstacles have been identified, such as limited facilities, a shortage of mental health workers, the absence of specialized shelters, and a weak, sustainable cross-sectoral coordination system.